Die antike Konzeption des Liebesbegriffes in der deutschen und russischen Literatur und Musik im 19. Jahrhundert anhand der Werke von E. T. A. Hoffmann, A. Puschkin, R. Schumann und P. Tschaikowski - Lukjanov, Julia (Q-Serie, 2010)
This work examines the expression of Love in an interdisciplinary approach to literature and music in Germany and Russia during the Romantic Period. The starting point is Socrates' classical discourse about Love and his definition of it, which Plato recorded in his Symposium. This will be applied to and examined in the Romantic Period, first in German and Russian literature and later in Music. What changes occur in the reception of this term? What differences or possible parallels can be determined in the two cultures and mentalities that are different at first sight? What is the influence of the respective artists on these changes? The results will be applied to the individual works of the writers A. Pushkin and E.T.A. Hoffmann as well as the musical settings of these works by the composers P. Tchaikovsky and R. Schumann. This examination, which is based primarily on literature and literary criticism, places the concept of Love in the foreground, even above the person or the work of the respective artist. Therefore, the primary goal of this work is to follow the reception of Plato's "theory of love" during the Romantic Period. The concepts of one's own inconstancy, the development of beauty, and the path of love correspond with the metacognitive philosophy of the Romantics. The subject of love has particular significance today because of the media's frequent discussions about the crisis of moral values. Love is transmedial. It transcends the subjective lives of humans, the objective external conditions, culture and mentality, literature and music; and it remains a desire, an ambition, an idea. Love is active and bridges every boundary as a communicational code or as nature's utmost attempt to lead an individual out of himself and to another.